Debatimos la fábula, el león enamorado - Díaz Cieza, José Feliciano (2019)
Today's societies bring us a series of limitations in the development of kills, values, attitudes, abilities and competences; which do not let us move on as a country full of opportunities. One of which Peruvians have great difficulty is precisely in the competence of the area of Communication in its competence communicates orally in their mother tongue._x000D_ It is for the above-mentioned that in the present learning strategy the debate has been placed as a main method, not only to improve verbal, communicative expression; but also, that the students are protagonists of the development of their own knowledge, consolidating the teacher as a mediating agent._x000D_ On the other hand, this work is based on theorists and pedagogues who give us a range of guidelines on how the educational process should be developed with children of all levels and educational cycles, within which we cite Minedu, Gálvez, García, Ausubel, Brunner, among others that is registered in the bibliography.